STROMATOLITES: Interaction of Microbes with Sediments - Tewari, Vinod; Seckbach, Joseph (Cellular Origin, Life in Extreme Habitats and Astrobiology,, 2011)
This book provides an overview and latest information about the formation of Stromatolites as a result of interaction of microbes with sediments. Eighty-three expert scientists from twenty-seven countries present the chapters in this volume which have been reviewed by thirty four referees. The volume deals with ancient to modern examples of stromatolites and microorganisms which are observed in various diverse environments, such as: marine, nonmarine, lacustrine and extreme geographical areas covering almost the whole earth. The reviews are original articles written by leading experienced experts, some chapters deal with latest instrumental techniques used for the study of microbes and Stromatolites. Other chapters have been contributed by young researchers who revealed updated data on Stromatolites. The astrobiological implications of early microbiota, sulfur isotopic ratios, microbialites in extreme conditions on earth has opened up new vistas in the search of extraterrestrial life. These chapters on biosedimentological, geomicrobiological, biogeochemical and astrobiological studies are aimed at biologists, under- and graduate geological students, researchers and professional scientists who need latest developments in the field of sedimentology and applied aspects.